Quaternary ammonium salt modified chitosan-based composite hydrogel and preparation method thereof
The combination of quaternary ammonium modified chitosan-based composite hydrogel and nanoparticles loaded with Centella asiaticin was solved, and the effect of scar-free wound healing was achieved.
Patent Information
- Application Number
- CN202411988957.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-02-07
AI Technical Summary
The prior art is difficult to achieve scar-free healing of wounds. Long-term inflammatory reactions will lead to the formation of scars and affect the beauty and function of the skin.
Quaternary ammonium modified chitosan-based composite hydrogel was used, which was prepared by mixing O-quaternary ammonium chitosan and 3-maleimidopropionic acid modified Plurandosaccharide, and nanoparticles loaded with Centella asiaticin were added to form a drug-loaded composite hydrogel.
This composite hydrogel has good self-healing, injectable, adhesion, antibacterial and other multifunctional properties, and can promote rapid and perfect wound healing in the mouse full-thickness skin injury model and reduce scar formation.
Smart Images

Figure CN119775641A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite hydrogel preparation, and specifically relates to a quaternary ammonium salt-modified chitosan-based composite hydrogel and a preparation method thereof. Background Art
[0002] The skin is the organ with the largest surface area in the human body. It plays an important role in protecting the body from mechanical damage, maintaining homeostasis, sensing external stimuli, and participating in immune responses. It is composed of the epidermis, dermis, and subcutaneous layer. Skin damage can be understood as a situation in which the normal skin function is damaged or disturbed by external factors such as chemical, physical, or thermal factors. The complete structure of the skin tissue is destroyed, resulting in a wound. Wound healing is carried out in a coordinated and orderly time series, which refers to the process of recovery and closure of the skin after damage. The whole process is divided into four stages, namely hemostasis, inflammation, proliferation, and remodeling. Among them, the inflammation stage is the key stage that affects the speed and perfection of wound healing. Long-term inflammatory response will lead to the formation of scars. The formation of scars not only affects the beauty and function of the skin, but also brings psychological pain to patients. Too many scars may even cause the loss of normal functions of the body.
[0003] Therefore, it is necessary to develop a new type of composite hydrogel that can achieve scar-free wound repair. Summary of the invention
[0004] The purpose of the present invention is to provide a quaternary ammonium salt modified chitosan-based composite hydrogel, and providing a preparation method thereof is another invention purpose of the present invention. The present invention prepares a novel hydrogel dressing with multifunctional properties such as self-healing, injectable, adhesive, and antibacterial properties based on quaternary ammonium salt chitosan and esterified pullulan. Studies have shown that when the nano-ions containing asiaticoside are added during the preparation of the hydrogel, the prepared drug-loaded composite hydrogel can achieve a scar-free wound healing effect.
[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical scheme:
[0006] A quaternary ammonium salt modified chitosan-based composite hydrogel, characterized in that the composite hydrogel is obtained by mixing an O-quaternary ammonium salt chitosan O-HACC solution and a pullulan PL-MA solution modified with 3-maleimidopropionic acid in a certain proportion and standing.
[0007] The mass volume fractions of the O-HACC solution and the PL-MA solution are 5 w / v% and 4 w / v%, respectively, and the mixing volume ratio of the O-HACC solution and the PL-MA solution is 1:1-4:1.
[0008] Before mixing, the nanoparticles loaded with asiaticaside were mixed with the PL-MA solution and then mixed with the O-HACC solution.
[0009] The nanoparticles loaded with asiaticoside are PDA@Zif-8-xAC, wherein x represents the concentration of asiaticoside added, the unit is mg / mL, and the value of x is 0.5-4.0.
[0010] The preparation method of the quaternary ammonium salt modified chitosan-based composite hydrogel comprises the following steps:
[0011] Step S1, preparing O-quaternary ammonium salt chitosan O-HACC:
[0012] (1) Weigh 2.0-4.0g chitosan and add it to 90-120mL deionized water, add 10-15mL glacial acetic acid solution, stir together at room temperature for 1-2h, place in a refrigerator at 4°C for 12-20h, add 90-120mL anhydrous ethanol and stir until a uniform system is obtained; take 10.0-12.0g benzaldehyde solution and dissolve it in 20-30mL anhydrous ethanol, and drip it into the chitosan solution within 2-3h, while adding it dropwise with high-speed magnetic stirring, after the addition is completed, stir the solution at 60-70°C for 8-10h, then add 100-120mL anhydrous ethanol to cool and terminate the reaction, then add 100-120mL 1mol / L NaOH solution to the solution to obtain a white precipitate, and wash the precipitate repeatedly with anhydrous ethanol for 4-5 times, vacuum dry the precipitate at 50-55°C for 48-50h, then add the dried product to 20-30mL 40w / v% NaOH solution, stirring at 55-65°C for 1.5-2.5h, then filtering, and vacuum drying the obtained product to obtain alkalized N-benzylidene chitosan Shiff-CS;
[0013] (2) Dispersing the dried N-benzylidene chitosan in 80-100 mL of isopropanol solution, stirring at room temperature for 1.5-2.5 h, adding 10.0-12.0 g of 2,3-epoxypropyltrimethylammonium chloride to the dispersion, placing the system in a 70° C. water bath and continuing to stir for 24-30 h, while using a condensation reflux device, cooling naturally to room temperature after the reaction is completed, precipitating the reaction mixture with acetone, filtering the precipitate, and washing with anhydrous ethanol, and vacuum drying the washed product to obtain quaternary ammonium salt-grafted N-benzylidene chitosan (Shiff-HACC);
[0014] (3) adding the obtained quaternary ammonium salt grafted N-benzylidene chitosan to 140-160 mL of 0.25 mol / L hydrochloric acid ethanol solution and stirring for 22-26 h, adjusting the pH of the system to neutral with a 1 g / mL Na2CO3 aqueous solution, precipitating with acetone again, washing until the pH of the filtrate is neutral, filtering and drying to obtain a crude product; dialyzing it in a dialysis bag with a molecular weight cutoff of 8-14 kD for 2-4 d, and freeze-drying the dialyzed product to obtain a purified product O-quaternary ammonium salt chitosan O-HACC;
[0015] Step S2: Preparation of PL-MA
[0016] First, 10.0-12.0 g of pullulan PL was weighed and added to 100-120 mL of dimethyl sulfoxide solution and stirred for 1-2 h. 3.0-4.0 g of N, N'-dicyclohexylcarbodiimide and 2.0-3.0 g of 1-hydroxybenzotriazole were added to the reaction solution and stirred for 1-2 h. 6.0-8.0 g of 3-maleimidopropionic acid MA was dissolved in 10-20 mL of dimethyl sulfoxide solution and added dropwise to the above reaction solution and stirred at 37° C. for 35-38 h. After the end, a dialysis bag with a molecular weight cutoff of 3 kD was used for dialysis for 4-6 days. The dialyzed product was freeze-dried to obtain a purified product, 3-maleimidopropionic acid-modified pullulan PL-MA.
[0017] Step S3: Preparation of PDA@Zif-8-xAC
[0018] (1) 3.94 g of 2-methylimidazole was weighed and dissolved in 40 mL of methanol solution. After stirring until completely dissolved, 1.31 g of zinc acetate dihydrate was added; stirring was continued at room temperature for 20-26 hours. After the reaction was completed, the mixture was centrifuged at a speed of 8000-9000 r / min for 8-12 minutes. The centrifugal precipitate was washed with methanol 2-4 times and vacuum dried at 55-65° C. for 12-14 hours. The obtained product was named Zif-8;
[0019] (2) 0.2-0.4 g Zif-8 was added to 40-60 mL anhydrous ethanol and stirred for 2-4 h, then 0.2-0.4 g dopamine hydrochloride was added and stirred for 25-35 min, then 20-160 mg asiaticoside was added and stirred for 1-1.5 h, the pH of the solution was adjusted to 8.0-9.0 with 0.8-1 mol / L sodium hydroxide solution, and the stirring was continued for 22-26 h. After the reaction was completed, the solution was washed with anhydrous ethanol while being centrifuged for 8-12 min at a speed of 8000-9000 r / min. The centrifugal precipitate was vacuum dried, and the obtained product was named PDA@Zif-8-xAC; wherein x represents the concentration of asiaticoside added, in mg / mL;
[0020] Step S4: preparing composite hydrogel
[0021] Select the following method A or method B to prepare the composite hydrogel:
[0022] Method A: First, 0.25 g of O-HACC and 0.2 g of PL-MA were dissolved in 5 mL of deionized water to form a 5 w / v% O-HACC homogeneous solution and a 4 w / v% PL-MA homogeneous solution, respectively. The two were then mixed in a certain proportion and allowed to stand to obtain a composite hydrogel. The obtained hydrogel was named O-HACC / PL-MAxy, hereinafter referred to as HPxy, where x and y represent the volumes of the O-HACC solution and the PL-MA solution added during gelation.
[0023] Method B: Weigh 0.1 g of PDA@Zif-8-xAC powder and add it to a total volume of 5 mL of 4 w / v% PLMA solution, then mix it with an equal volume of 5 w / v% O-HACC solution to form a gel. The resulting hydrogel is named AA@O-HACC / PL-MA11, abbreviated as AA@HP11.
[0024] Compared with the prior art, the present invention has the following technical effects:
[0025] 1) The present invention simply mixes the OHACC solution and the PL-MA solution, and utilizes the reaction of the groups between the two compounds to quickly prepare a composite hydrogel. The hydrogel has a connected porous structure, good self-healing properties, injectability, adhesion, antibacterial properties and biocompatibility.
[0026] 2) After the hydrogel of the present invention in situ encapsulates nanoparticles containing asiaticoside, it is found through a mouse full-thickness skin injury model that the drug-loaded hydrogel of the present invention can promote rapid and perfect wound healing. Immunohistochemical staining found that the drug-loaded hydrogel can upregulate CD31 expression and downregulate TGF-β1 and α-SMA expression to promote scar-free wound repair. This provides a new means for subsequent research on the use of hydrogel dressings for scar-free wound repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Nanoparticle drug loading test. (a) Particle size distribution; (b) Asiaticoside release curve; (c) Drug loading statistics; (d) Drug loading efficiency statistics;
[0028] Figure 2 Preparation and morphological characterization of hydrogel. (a) FT-IR spectrum of HP hydrogel; (b) macroscopic image of HP hydrogel; (c) microscopic morphology of hydrogel (scale bar of the first row = 250 μm, scale bar of the second row is the enlarged image = 500 μm);
[0029] Figure 3Rheological tests of composite hydrogels. (a) and (b) frequency scanning mode and strain scanning mode of HP hydrogel; (c) and (d) frequency scanning mode and strain scanning mode of AA@HP11 hydrogel;
[0030] Figure 4 Hydrogel self-healing test. Rheological step cycle mode (a) HP11; (b) AA@HP11; macroscopic self-healing photo (c) HP11; (d) AA@HP11;
[0031] Figure 5 Hydrogel adhesion and injectability test. (a) Photographs of HP hydrogel adhesion to glass, metal, plastic, and human skin; (b) Rheological shear-thinning test (the picture shows a schematic diagram of hydrogel injectability);
[0032] Figure 6 Antibacterial properties of hydrogels. (a) Photo of co-culture of bacterial colonies and hydrogels in glass test tubes (Escherichia coli on the left and Staphylococcus aureus on the right); (b) Statistics of the inhibition rates of Escherichia coli and Staphylococcus aureus;
[0033] Figure 7 Cell activity evaluation. (a) In vitro cytotoxicity of HP hydrogel extract co-cultured with HUVEC cells for 24h and 48h; (b) Fluorescence staining images of HUVEC cells at 24h and 48h of culture (scale bar = 200μm);
[0034] Figure 8 Cell scratch healing experiment. (a) Scratch healing images of HP hydrogel extract and HUVEC cells co-cultured for 6h and 24h (scale bar = 100μm); (b) Quantitative statistics of HUVEC cell healing;
[0035] Fig. 9 In vivo animal model healing experiment. (a) Schematic diagram of the process of establishing a mouse wound healing model; (b) Photos of mouse wound healing at different time periods; (c) Schematic diagram of wound healing at different time periods; (d) Statistics of wound healing area at different time points;
[0036] Fig.10 Histopathological analysis. (a) H&E (b) Masson staining images (scale bars: 4 mm and 400 μm); (c) Statistical data of wound epithelial tissue thickness; (d) Statistical data of wound hair follicle number; (e) Statistical data of wound collagen ratio;
[0037] Fig.11Immunohistochemical staining analysis of wounds on day 12. (a) CD31, (b) TGF-β1, (c) α-SMA staining images (scale bar: 100 μm); (d) Quantitative analysis of CD31, (e) TGF-β1, (f) α-SMA expression levels. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below in conjunction with the accompanying drawings.
[0039] Example 1
[0040] A quaternary ammonium salt modified chitosan-based composite hydrogel of this embodiment is obtained by mixing an O-quaternary ammonium salt chitosan O-HACC solution and a 3-maleimidopropionic acid modified pullulan PL-MA solution in a certain proportion and standing. The preparation method thereof comprises the following steps:
[0041] Step S1, preparing O-quaternary ammonium salt chitosan (O-HACC):
[0042] (1) Weigh 2.0 g of chitosan and add it to 90 mL of deionized water, add 10 mL of glacial acetic acid solution at the same time, stir together at room temperature for 1 h, place in a refrigerator at 4°C for 18 h, then add 100 mL of anhydrous ethanol and stir until a uniform system is obtained; take 10.0 g of benzaldehyde solution and dissolve it in 20 mL of anhydrous ethanol, and drop it into the chitosan solution within 2-3 h, while adding it dropwise with high-speed magnetic stirring, after the addition is completed, stir the solution at 60°C for 10 h, then add 100 mL of anhydrous ethanol to cool down and terminate the reaction, then add 100 mL of 1 mol / L NaOH solution to the solution to obtain a white precipitate, and wash the precipitate repeatedly with anhydrous ethanol for 5 times, then vacuum dry the product at 50°C for 48 h, then add the dried product to 20 mL of 40 w / v% NaOH solution, stir it at 60°C for 2 h, and then filter it, and vacuum dry the obtained product to obtain alkalized N-benzylidene chitosan (Shiff-CS);
[0043] (2) Dispersing the dried N-benzylidene chitosan in 100 mL of isopropanol solution, stirring at room temperature for 2 h, adding 10.0 g of 2,3-epoxypropyltrimethylammonium chloride to the dispersion, and then placing the system in a 70°C water bath and continuing to stir for 24-30 h, while using a condensation reflux device. After the reaction is completed, naturally cool to room temperature, use acetone to precipitate the reaction mixture, filter the precipitate, and wash it with anhydrous ethanol. The washed product is vacuum dried to obtain quaternary ammonium salt-grafted N-benzylidene chitosan (Shiff-HACC);
[0044] (3) adding the obtained quaternary ammonium salt grafted N-benzylidene chitosan to 150 mL of 0.25 mol / L hydrochloric acid ethanol solution and stirring for 24 h, adjusting the pH of the system to neutral with 1 g / mL Na2CO3 aqueous solution, precipitating with acetone again, washing until the pH of the filtrate is neutral, filtering and drying to obtain a crude product; dialyzing it in a dialysis bag with a molecular weight cutoff of 8-14 kD for 3 d, and freeze-drying the dialyzed product to obtain a purified product O-quaternary ammonium salt chitosan O-HACC;
[0045] Step S2: Preparation of PL-MA
[0046] First, 10.0 g of pullulan PL was weighed and added to 100 mL of dimethyl sulfoxide solution and stirred for 1 h. 3.0 g of N, N'-dicyclohexylcarbodiimide and 2.0 g of 1-hydroxybenzotriazole were added to the reaction solution and stirred for 1 h. 6.0 g of 3-maleimidopropionic acid MA was dissolved in 10 mL of dimethyl sulfoxide solution and added dropwise to the above reaction solution and stirred at 37° C. for 36 h. After the end, the solution was dialyzed for 5 days using a dialysis bag with a molecular weight cutoff of 3 kD. The dialyzed product was freeze-dried to obtain the purified product 3-maleimidopropionic acid-modified pullulan PL-MA.
[0047] Step S3: preparing composite hydrogel
[0048] First, 0.25 g of O-HACC and 0.2 g of PL-MA were dissolved in 5 mL of deionized water to form a 5 w / v% O-HACC homogeneous solution and a 4 w / v% PL-MA homogeneous solution, respectively. The two were then mixed in a certain proportion and allowed to stand to obtain a composite hydrogel. The resulting hydrogel was named O-HACC / PL-MAxy, hereinafter referred to as HPxy, where x and y represent the volumes of the O-HACC solution and the PL-MA solution added during gelation.
[0049] Example 2
[0050] The quaternary ammonium salt modified chitosan-based composite hydrogel of this embodiment is the same as that of embodiment 1, except that, before mixing, the nanoparticles PDA@Zif-8-xAC loaded with asiaticoside and the PL-MA solution are first mixed, and then mixed with the O-HACC solution. Wherein, x represents the concentration of asiaticoside added, in mg / mL, and the value of x is 0.5-4.0, and in this embodiment, it is 2.0.
[0051] The preparation method of nanoparticles PDA@Zif-8-xAC loaded with asiatica glycoside is as follows:
[0052] (1) Weigh 3.94 g of 2-methylimidazole and dissolve it in 40 mL of methanol solution. After stirring until it is completely dissolved, add 1.31 g of zinc acetate dihydrate; continue stirring at room temperature for 24 hours. After the reaction is completed, centrifuge at 8500 r / min for 10 minutes. Wash the centrifugal precipitate with methanol three times and vacuum dry it at 60° C. for 12 hours. The obtained product is named Zif-8;
[0053] (2) 0.2 g of Zif-8 was added to 40 mL of anhydrous ethanol and stirred for 3 h, then 0.2 g of dopamine hydrochloride was added and stirred for 30 min, then 80 mg of asiaticoside was added and stirred for 1 h, the pH of the solution was adjusted to 8.5 with 1 mol / L sodium hydroxide solution, and stirring was continued for 24 h. After the reaction was completed, the solution was washed with anhydrous ethanol while centrifuging. Washing with anhydrous ethanol while centrifuging means that the reaction was completed and the precipitate was washed with anhydrous ethanol and centrifuged again, and the washing with anhydrous ethanol was repeated. In this embodiment, the process was repeated three times, each time with a centrifugation time of 10 min and a rotation speed of 8500 r / min. The centrifuged precipitate was vacuum dried, and the obtained product was named PDA@Zif-8-2.0AC; wherein 2.0 represents the concentration of asiaticoside added, in mg / mL, i.e., the ratio of the mass of asiaticoside to the methanol solution.
[0054] When preparing the hydrogel, 0.1 g of PDA@Zif-8-xAC powder was weighed and added to a total volume of 5 mL of PLMA solution with a concentration of 4 w / v%, and then mixed with an equal volume of O-HACC solution with a concentration of 5 w / v% to form a gel. The resulting hydrogel was named AA@O-HACC / PL-MA11, abbreviated as AA@HP11.
[0055] Example 3
[0056] The quaternary ammonium salt modified chitosan-based composite hydrogel of this embodiment is the same as that of embodiment 1, except that, step S1, preparation of O-quaternary ammonium salt chitosan O-HACC:
[0057] (1) Weigh 2.0 g of chitosan and add it to 90 mL of deionized water, add 10 mL of glacial acetic acid solution at the same time, stir together at room temperature for 1 h, place in a refrigerator at 4°C for 12 h, add 90 mL of anhydrous ethanol and stir until a uniform system is obtained; take 10.0 g of benzaldehyde solution and dissolve it in 20 mL of anhydrous ethanol, and drop it into the chitosan solution within 2 h, while adding it dropwise with high-speed magnetic stirring, after the addition is completed, stir the solution at 60°C for 8 h, then add 100 mL of anhydrous ethanol to cool down and terminate the reaction, then add 100 mL of 1 mol / L NaOH solution to the solution to obtain a white precipitate, and wash the precipitate repeatedly with anhydrous ethanol for 4 times, and vacuum dry the precipitate at 50°C for 48 h, then add the dried product to 20 mL of 40 w / v% NaOH solution, stir it at 55-65°C for 1.5 h, and then filter it, and vacuum dry the obtained product to obtain alkalized N-benzylidene chitosan Shiff-CS;
[0058] (2) Dispersing the dried N-benzylidene chitosan in 80 mL of isopropanol solution, stirring at room temperature for 1.5 h, adding 10.0 g of 2,3-epoxypropyltrimethylammonium chloride to the dispersion, placing the system in a 70°C water bath and continuing to stir for 24 h, while using a condensation reflux device, cooling naturally to room temperature after the reaction is completed, precipitating the reaction mixture with acetone, filtering the precipitate, and washing with anhydrous ethanol, and vacuum drying the washed product to obtain quaternary ammonium salt-grafted N-benzylidene chitosan (Shiff-HACC);
[0059] (3) adding the obtained quaternary ammonium salt grafted N-benzylidene chitosan to 140 mL of 0.25 mol / L hydrochloric acid ethanol solution and stirring for 22 h, then adjusting the pH of the system to neutral with a 1 g / ml Na2CO3 aqueous solution, precipitating with acetone again, then washing until the pH of the filtrate is neutral, filtering and drying to obtain a crude product; dialyzing it in a dialysis bag with a molecular weight cutoff of 8 kD for 2-4 d, and freeze-drying the dialyzed product to obtain a purified product O-quaternary ammonium salt chitosan O-HACC;
[0060] Step S2: Preparation of PL-MA
[0061] First, 10.0 g of pullulan PL was weighed and added to 100 mL of dimethyl sulfoxide solution and stirred for 1 h. 3.0 g of N, N'-dicyclohexylcarbodiimide and 2.0 g of 1-hydroxybenzotriazole were added to the reaction solution and stirred for 1 h. 6.0 g of 3-maleimidopropionic acid MA was dissolved in 10 mL of dimethyl sulfoxide solution and added dropwise to the above reaction solution and stirred at 37° C. for 35 h. After the end, the solution was dialyzed for 4 days using a dialysis bag with a molecular weight cutoff of 3 kD. The dialyzed product was freeze-dried to obtain the purified product 3-maleimidopropionic acid-modified pullulan PL-MA.
[0062] Example 4
[0063] The quaternary ammonium salt modified chitosan-based composite hydrogel of this embodiment is the same as that of embodiment 1, except that, step S1, preparation of O-quaternary ammonium salt chitosan O-HACC:
[0064] (1) Weigh 4.0 g of chitosan and add it to 120 mL of deionized water, add 15 mL of glacial acetic acid solution at the same time, stir together at room temperature for 2 h, place in a refrigerator at 4 ° C for 20 h, add 120 mL of anhydrous ethanol and stir until a uniform system is obtained; take 12.0 g of benzaldehyde solution and dissolve it in 30 mL of anhydrous ethanol, and drop it into the chitosan solution within 3 h, while adding it dropwise with high-speed magnetic stirring, after the addition is completed, stir the solution at 70 ° C for 10 h, then add 120 mL of anhydrous ethanol to cool and terminate the reaction, then add 120 mL of 1 mol / L NaOH solution to the solution to obtain a white precipitate, and wash the precipitate repeatedly with anhydrous ethanol for 5 times, and vacuum dry the precipitate at 55 ° C for 50 h, then add the dried product to 30 mL of 40 w / v% NaOH solution, stir it at 65 ° C for 2.5 h, and then filter it, and vacuum dry the obtained product to obtain alkalized N-benzylidene chitosan Shiff-CS;
[0065] (2) Dispersing the dried N-benzylidene chitosan in 100 mL of isopropanol solution, stirring at room temperature for 2.5 h, adding 12.0 g of 2,3-epoxypropyltrimethylammonium chloride to the dispersion, placing the system in a 70°C water bath and continuing to stir for 30 h, while using a condensation reflux device, cooling naturally to room temperature after the reaction is completed, precipitating the reaction mixture with acetone, filtering the precipitate, and washing with anhydrous ethanol, and vacuum drying the washed product to obtain quaternary ammonium salt-grafted N-benzylidene chitosan (Shiff-HACC);
[0066] (3) adding the obtained quaternary ammonium salt grafted N-benzylidene chitosan to 160 mL of 0.25 mol / L hydrochloric acid ethanol solution and stirring for 26 h, then adjusting the pH of the system to neutral with a 1 g / mL Na2CO3 aqueous solution, precipitating with acetone again, then washing until the pH of the filtrate is neutral, filtering and drying to obtain a crude product; dialyzing it in a dialysis bag with a molecular weight cutoff of 8-14 kD for 4 days, and freeze-drying the dialyzed product to obtain a purified product O-quaternary ammonium salt chitosan O-HACC;
[0067] Step S2: Preparation of PL-MA
[0068] First, 12.0 g of pullulan PL was weighed and added to 120 mL of dimethyl sulfoxide solution and stirred for 2 h. 4.0 g of N, N'-dicyclohexylcarbodiimide and 2.0-3.0 g of 1-hydroxybenzotriazole were added to the reaction solution and stirred for 2 h. 8.0 g of 3-maleimidopropionic acid MA was dissolved in 20 mL of dimethyl sulfoxide solution and added dropwise to the above reaction solution and stirred at 37 ° C for 38 h. After the end, dialyzed for 6 days using a dialysis bag with a molecular weight cutoff of 3 kD. The dialyzed product was freeze-dried to obtain the purified product 3-maleimidopropionic acid modified pullulan PL-MA.
[0069] Comparative Example 1 Preparation of drug-loaded nanoparticles of different concentrations
[0070] The method is the same as the step of preparing PDA@Zif-8-xAC in Example 2, except that, when other conditions remain unchanged, 160 mg, 40 mg, and 20 mg of asiaticoside are added respectively to prepare drug-loaded nanoparticles of different concentrations as the experimental control group, and a blank control group without asiaticoside is used as the blank control group, named PDA@Zif-8;
[0071] Performance Testing
[0072] 1. Test of drug loading of nanoparticles at different concentrations
[0073] The PDA@Zif-8-xAC nanoparticles of the present invention firstly modify the Zif-8 nanoparticles and PDA by a one-pot method, and then introduce the AC modification into the PDA@Zif-8 surface. The morphology of Zif-8, PDA@Zif-8 and PDA@Zif-8-xAC was observed by TEM. On this basis, the size of the nanoparticles was further tested and analyzed ( Figure 1 a). The average particle size of Zif-8 is about 220nm, while due to the addition of PDA, the average particle size of PDA@Zif-8 increases to about 825nm. After AC modification, the particle size of PDA@Zif-8-xAC nanoparticles increases according to the amount of AC added. In addition, the experimental results show that the release performance of PDA@Zif-8-xAC nanoparticles increases with the increase of AC content ( Figure 1 b) Drug loading ( Figure 1 c) and drug loading efficiency ( Figure 1d) also increased. The drug loading of PDA@Zif-8-4.0AC, PDA@Zif-8-2.0AC, PDA@Zif-8-1.0AC and PDA@Zif-8-0.5AC were 76.85218±4.41532mg, 68.11249±1.72351mg, 34.18581±0.74217mg and 17.99176±0.9818mg, respectively. The results show that increasing the concentration of asiaticoside in the solution in the loading experiment can significantly increase the drug loading of PDA@Zif-8 nanoparticles. However, by comparing the drug loading data of PDA@Zif-8-4.0AC and PDA@Zif-8-2.0AC, it can be seen that when the concentration of asiaticoside increases to a certain level, the MOF structure of PDA@Zif-8 nanoparticles has reached the maximum drug loading capacity. The drug loading increases less significantly as the concentration of asiaticoside in the solution continues to increase. From the above drug loading results, it can be concluded that there is a significant difference between the drug loading efficiency of asiaticoside and its addition amount, so the drug loading efficiency of PDA@Zif-8 nanoparticles was further tested. The drug loading efficiencies of PDA@Zif-8-4.0AC, PDA@Zif-8-2.0AC, PDA@Zif-8-1.0AC and PDA@Zif-8-0.5AC were 48.03261±2.75958%, 85.14061±2.15439%, 85.46452±1.85543%, and 89.95878±4.90901%, respectively. It can be found that the loading efficiency of PDA@Zif-8-4.0AC is significantly reduced, which is mainly because the drug loading of PDA@Zif-8 nanoparticles has reached the upper limit. Even if the solution concentration is increased, the drug loading amount does not increase significantly, so the loading efficiency is sharply reduced. In summary, comparing all the test results, it can be seen that the present invention selects PDA@Zif-8-2.0AC as the best experimental scheme to participate in the subsequent preparation of drug-loaded hydrogels.
[0074] 2. Preparation and morphology characterization of hydrogel
[0075] The preparation and morphology characterization results of the hydrogel are shown in Figure 2 As shown. O-HACC and PL-MA solutions were mixed at room temperature in a certain proportion to prepare HP composite hydrogel. The reaction mechanism is that the amino group on O-HACC and the double bond on PL-MA undergo Michael addition reaction. In the FT-IR spectrum of HP hydrogel ( Figure 1 a), PL-MA at 1700 cm -1 The double bond peak at 1070-1156cm disappeared, which may be consumed by the reaction during gelation. -1The peak stretching vibration at becomes more obvious, which may be caused by the increase of newly generated carbon-nitrogen single bonds. At the same time, after mixing the prepared solution and inverting it for a period of time, it was found that the solution did not flow along the wall of the test tube ( Figure 2 b), indicating that the two have completely reacted and formed a new colloidal product. The above results all indicate that the preparation of HP hydrogel is successful.
[0076] Microscopic observation of the hydrogel morphology ( Figure 2 c) It was found that the interior of all hydrogels is interconnected and porous. As a wound dressing, the porous structure is conducive to promoting the circulation of oxygen, water and nutrients, and can also maintain a moist environment for the wound. Comparing AA@HP11 hydrogel and HP hydrogel, both are porous structures, but through the magnified SEM image, it can be found that the surface of HP hydrogel is smooth while the surface of AA@HP11 hydrogel is rugged, indicating that the drug is successfully loaded.
[0077] 3. Analysis of rheological properties of composite hydrogel
[0078] When hydrogel is used for wound dressing, it needs to have a certain rigidity to avoid deformation or breakage due to external forces in a dynamic environment, so as to better protect the wound. The hydrogel is subjected to two rheological sweep tests: frequency and strain. In the frequency sweep mode ( Figure 3 a, c), set the temperature constant (37℃) and strain constant (1%); the storage modulus (G') of the hydrogel before structural destruction is higher than the loss modulus (G"), indicating that all hydrogel materials have relatively stable structures and good mechanical properties. Among the HP hydrogels, the highest G' of HP11 is about 100Pa, while the highest G' of AA@HP11 hydrogel is about 4200Pa, which is much higher than that of HP hydrogel. This is because the addition of nanoparticles enhances the mechanical strength of the hydrogel. In the strain scanning mode ( Figure 3 b, d), set the temperature constant (37°C) and frequency constant (1Hz), as the force intensity continues to increase, the hydrogel gradually reaches the maximum force it can withstand, and eventually the three-dimensional network is destroyed. HP11 breaks at about 650%, HP21 at about 400%, HP41 at about 140%, and AA@HP11 at about 160%. The frequency and strain test results show that hydrogels have great advantages in promoting skin wound healing.
[0079] 4. Analysis of self-healing properties of composite hydrogel
[0080] Self-healing hydrogels have good physical and biological properties, which can maintain the integrity of structure and function on the one hand, and extend the life of materials on the other hand. Figure 4As shown in a, the rheological test results show that when the strain is set to 1%, the storage modulus (G') is significantly higher than the loss modulus (G"), indicating that the sample exhibits typical solid hydrogel properties at this strain, with strong elasticity and a stable network structure. However, when the strain increases to 1000%, the G' value decreases, showing that the elasticity of the hydrogel is significantly weakened, and the G" value exceeds G', indicating that the cross-linked network structure of the hydrogel is destroyed under a larger strain, and the hydrogel exhibits typical fluid behavior and loses its original solid form. The same behavior was also observed in the rheological step test of AA@HP11 hydrogel ( Figure 4 b). All these indicate that the hydrogel has good self-healing properties, and the addition of nanoparticles does not affect this property. When the hydrogel is cut and reassembled, it can also be found that the composite hydrogel can self-heal ( Figure 4 c, d). The self-healing ability of the hydrogel comes from the reversible hydrogen bonding interaction between molecules.
[0081] 5. Analysis of adhesion and injectability of composite hydrogel
[0082] The adhesion of the hydrogel can help it fix on the wound surface to avoid slipping or displacement, thereby improving the healing effect on the damaged tissue. The adhesion properties of the hydrogel were characterized by macroscopic adhesion experiments. Figure 5 As shown in a, the prepared hydrogel can adhere to objects of different materials such as glass, metal, and plastic, and can also adhere to human skin without falling off. This shows that the HP composite hydrogel has good adhesion properties. Injectable hydrogels have the advantages of fluidizing under shear stress and then recovering the original mechanical properties, and can be accurately applied to irregularly shaped wound defects in a highly controlled manner. The injectable properties of HP hydrogels were verified by rheological shear-thinning tests ( Figure 5 b) It was found that at 37°C, the shear rate range was 0.1-100 s -1 The viscosity of HP hydrogel decreases with the increase of shear rate. This shear thinning behavior shows that HP hydrogel has good injectability. Using a 0.5×24 inch syringe, the hydrogel can be easily drawn into a "five-pointed star" pattern ( Figure 5 b illustration).
[0083] 6. Analysis of antibacterial properties of composite hydrogel
[0084] Antibacterial hydrogel is important in wound healing. It not only provides the necessary moist environment to promote healing, but also effectively prevents bacterial infection and reduces the inflammatory response and delayed healing caused by infection. The antibacterial ability of hydrogel is evaluated by co-culturing bacterial solution with samples. Figure 6 As shown in a, the bacterial solution in the control group is more turbid, while the experimental group with hydrogel added is clearer. This shows that HP hydrogel has good antibacterial ability. According to the statistics of antibacterial rate ( Figure 6 b), HP11 hydrogel showed the best antibacterial effect on Escherichia coli and Staphylococcus aureus, with the inhibition rates of 69.85±7.33% and 76.60±1.55%, respectively. In addition, HP21 hydrogel also had a higher inhibition ability against both bacteria than HP41 hydrogel. When co-cultured with Escherichia coli, HP21 was 46.86±16.06% and HP41 was 29.21±5.54%; when co-cultured with Staphylococcus aureus, HP21 was 68.60±7.18% and HP41 was 55.41±3.59%. The antibacterial ability of HP hydrogel is due to the antibacterial ability of chitosan itself and the introduction of quaternary ammonium ions that increase the antibacterial ability of the material.
[0085] 6. Biocompatibility analysis of composite hydrogel
[0086] Biocompatibility and safety are essential properties for hydrogels to be used as wound dressings. The hydrogel extract was co-cultured with HUVEC cells to verify the cytotoxicity of the HP hydrogel. The survival rate of HUVEC cells was evaluated using the CCK-8 cell proliferation assay kit. After 24h and 48h of co-culture, the survival rate of all cells was higher than 100% ( Figure 7 a), and there was no difference with the control group, indicating that the hydrogel had good biocompatibility. At the same time, the live / dead cell activity of the above cultured cells was detected, and the live cells and dead cells were marked with green and red fluorescent dyes, respectively. Figure 7 As shown in Figure b, most cells were stained green, and almost no dead cells were found. These experimental results prove that HP hydrogel has excellent biocompatibility and is not dangerous to use in wound dressings. Cell scratch healing experiments can further verify the cytotoxicity of HP hydrogel. The hydrogel extract was co-cultured with HUVEC cells for 6h and 24h. Figure 8 As shown in a, the cells showed a trend of migration and healing, among which HP11 hydrogel had the best healing effect. In particular, after 24h of co-culture, the migration number of HP11 was 634 ( Figure 8 b) HP hydrogels can promote the migration of endothelial cells, which is also critical for the use of hydrogels for wound healing.
[0087] 7. In vivo wound healing analysis
[0088] The effect of hydrogel dressing loaded with Centella asiatica on scarless wound healing was evaluated by a mouse wound healing model experiment. A full-thickness skin wound with a diameter of 1 cm was made on the back of the mouse. The wound was then treated with normal saline in the control group and HP11 hydrogel and AA@HP11 hydrogel in the experimental group, respectively. The wound healing was recorded with a digital camera at 0, 3, 6, 9, and 12 days after surgery ( Fig. 9 a) Wound healing results at different time periods during the experiment Fig. 9 As shown in bd, the wound area of each group began to decrease on the 3rd day, indicating that the wound was slowly healing. On the 6th day, the wound area further shrank, and the trend of the wound area of the experimental group being smaller than that of the control group became obvious. On the 9th day, the wound area of the experimental group using AA@HP11 hydrogel was 13.48 mm 2 , HP11 hydrogel is 21.51mm 2 , the control group was 39.28mm 2 . This indicates that the drug-loaded hydrogel promotes wound healing faster. On the 12th day, the wounds in the control group were still not completely healed, while the wounds in the AA@HP11 hydrogel group and the HP11 hydrogel group were almost completely healed. More importantly, compared with the HP11 hydrogel group, the AA@HP11 hydrogel group produced almost no scars. This indicates that the AA@HP11 hydrogel loaded with Centella asiatica promotes scar-free wound healing.
[0089] 8. Histological analysis
[0090] The degree of wound healing was further evaluated by histological analysis, including H&E staining and Masson staining. H&E staining was performed on the healed rat skin after different treatments on days 6 and 12, respectively. Fig.10 a). The integrity and thickness of the epidermis are important indicators for evaluating the degree of wound healing. As shown in the figure, the AA@HP11 group showed the best histological results, and more wound fiber production was observed ( Fig.10 c) and the presence of a large number of hair follicles in the granulation tissue ( Fig.10 d) To further explore the healing ability of AA@HP11, Masson staining was used to analyze the collagen deposition in skin tissue. Fig.10 b's display image and Fig.10 From the quantitative statistical results of e, it can be seen that collagen deposition was almost undetectable in the control group. However, the degree of collagen deposition in the HP11 group increased significantly, and the AA@HP11 group showed the highest level of collagen deposition, indicating that AA@HP11 achieved ideal wound healing efficiency by accelerating the reconstruction of the extracellular matrix and tissue remodeling.
[0091] 9. Immunohistochemical analysis
[0092] CD31 is a transmembrane protein widely expressed on the surface of vascular endothelial cells, platelets and immune cells. It is involved in cell-cell adhesion, platelet aggregation, vascular endothelial stability and immune response regulation, and plays an important role in angiogenesis in wound healing. Therefore, CD31 antibody was used to slice the wound healing tissue of mice on the 12th day for immunofluorescence staining to evaluate the formation of new blood vessels. Fig.11As shown in a and d, compared with the control group and HP11 hydrogel group, the CD31 expression level in the wound tissue of mice treated with the AA@HP11 hydrogel group was the highest on the 12th day, indicating that there was more regeneration of new blood vessels, which was beneficial to the rapid repair of damaged tissue and promoted wound healing. TGF-β1 is a key regulator in the process of wound healing and tissue repair, but the balance of its expression is very important. Excessive TGF-β1 expression can lead to excessive collagen synthesis and fibrosis, which in turn causes scar formation and fibrotic diseases. TGF-β1 immunohistochemical staining was performed on the mouse wound group, and the results of the control group, HP11 hydrogel group and AA@HP11 hydrogel group are shown in Figure 2. Fig.11 As shown in b and e, it is obvious that the expression of TGF-β1 in the AA@HP11 hydrogel group is lower than that in the first two groups, indicating that the hydrogel loaded with Centella asiatica can inhibit the expression of TGF-β1, thereby achieving anti-fibrosis and reducing the effect of scar formation. α-SMA (smooth muscle cell α-actin) is a marker of myofibroblasts. Myofibroblasts play an important role in wound healing and scar formation. They can promote wound healing and produce a large amount of collagen through contraction to repair damaged tissues. However, excessive myofibroblasts and α-SMA expression will lead to scar proliferation. Therefore, studying the expression of α-SMA is of great significance for exploring the effect of scarless wound healing. The results of α-SMA immunohistochemical staining show that ( Fig.11 c,f) The expression of α-SMA in the AA@HP11 hydrogel group was the lowest, indicating that AA@HP11 hydrogel has great potential in reducing scar formation. In summary, the above results all indicate that AA@HP11 hydrogel has a positive effect on promoting scar-free wound healing, which may be due to the role of Centella asiatica glycoside.
[0093] In summary, the present invention simply mixes OHACC solution and PL-MA solution, and quickly prepares a composite hydrogel by utilizing the reaction of the groups between the two compounds. Subsequently, through a series of related studies, it was found that the hydrogel has a connected porous structure, good self-healing performance, injectability, adhesion performance, antibacterial performance and biocompatibility. In addition, after the hydrogel is in situ encapsulated with nanoparticles containing Centella asiatica glycoside, it is found that the drug-loaded hydrogel can promote rapid and perfect healing of wounds through a mouse full-thickness skin injury model. Immunohistochemical staining found that the drug-loaded hydrogel can upregulate CD31 expression and downregulate TGF-β1 and α-SMA expression to promote scar-free wound repair.
[0094] The above embodiments provided by the present invention are only preferred embodiments of the present invention, and are not intended to limit the present invention in other forms. Any person skilled in the art can use the above disclosed technical contents to change or modify them into equivalent embodiments with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A quaternary ammonium salt modified chitosan-based composite hydrogel, characterized in that: The composite hydrogel is obtained by mixing an O-quaternary ammonium salt chitosan O-HACC solution and a 3-maleimidopropionic acid modified pullulan PL-MA solution in a certain proportion and allowing the mixture to stand.
2. The quaternary ammonium salt modified chitosan-based composite hydrogel according to claim 1, characterized in that: The mass volume fractions of the O-HACC solution and the PL-MA solution are 5 w / v% and 4 w / v%, respectively, and the mixing volume ratio of the O-HACC solution and the PL-MA solution is 1:1-4:
1.
3. The quaternary ammonium salt modified chitosan-based composite hydrogel according to claim 2, characterized in that: Before mixing, the nanoparticles loaded with asiaticaside were mixed with the PL-MA solution and then mixed with the O-HACC solution.
4. The quaternary ammonium salt modified chitosan-based composite hydrogel according to claim 3, characterized in that: The nanoparticles loaded with asiaticoside are PDA@Zif-8-xAC, wherein x represents the concentration of asiaticoside added, the unit is mg / mL, and the value of x is 0.5-4.
0.
5. The method for preparing the quaternary ammonium salt modified chitosan-based composite hydrogel according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step S1, preparing O-quaternary ammonium salt chitosan O-HACC: (1) Weigh 2.0-4.0g chitosan and add it to 90-120mL deionized water, add 10-15mL glacial acetic acid solution, stir together at room temperature for 1-2h, place in a refrigerator at 4°C for 12-20h, add 90-120mL anhydrous ethanol and stir until a uniform system is obtained; take 10.0-12.0g benzaldehyde solution and dissolve it in 20-30mL anhydrous ethanol, and drip it into the chitosan solution within 2-3h, while adding it dropwise with high-speed magnetic stirring, after the addition is completed, stir the solution at 60-70°C for 8-10h, then add 100-120mL anhydrous ethanol to cool and terminate the reaction, then add 100-120mL 1mol / L NaOH solution to the solution to obtain a white precipitate, and wash the precipitate repeatedly with anhydrous ethanol for 4-5 times, vacuum dry the precipitate at 50-55°C for 48-50h, then add the dried product to 20-30mL 40w / v% NaOH solution, stirring at 55-65°C for 1.5-2.5h, then filtering, and vacuum drying the obtained product to obtain alkalized N-benzylidene chitosan Shiff-CS; (2) Dispersing the dried N-benzylidene chitosan in 80-100 mL of isopropanol solution, stirring at room temperature for 1.5-2.5 h, adding 10.0-12.0 g of 2,3-epoxypropyltrimethylammonium chloride to the dispersion, placing the system in a 70° C. water bath and continuing to stir for 24-30 h, while using a condensation reflux device, cooling naturally to room temperature after the reaction is completed, precipitating the reaction mixture with acetone, filtering the precipitate, and washing with anhydrous ethanol, and vacuum drying the washed product to obtain quaternary ammonium salt-grafted N-benzylidene chitosan (Shiff-HACC); (3) adding the obtained quaternary ammonium salt-grafted N-benzylidene chitosan to 140-160 mL of 0.25 mol / L hydrochloric acid ethanol solution and stirring for 22-26 h, then adjusting the pH of the system to neutral with a 1 g / mL Na2CO3 aqueous solution, precipitating with acetone again, then washing until the pH of the filtrate is neutral, filtering with suction and drying to obtain a crude product; The product was dialyzed in a dialysis bag with a molecular weight cutoff of 8-14 kD for 2-4 days, and the dialyzed product was freeze-dried to obtain the purified product O-quaternary ammonium salt chitosan O-HACC; Step S2: Preparation of PL-MA First, 10.0-12.0 g of pullulan PL was weighed and added to 100-120 mL of dimethyl sulfoxide solution and stirred for 1-2 h. 3.0-4.0 g of N, N'-dicyclohexylcarbodiimide and 2.0-3.0 g of 1-hydroxybenzotriazole were added to the reaction solution and stirred for 1-2 h. 6.0-8.0 g of 3-maleimidopropionic acid MA was dissolved in 10-20 mL of dimethyl sulfoxide solution and added dropwise to the above reaction solution and stirred at 37° C. for 35-38 h. After the end, a dialysis bag with a molecular weight cutoff of 3 kD was used for dialysis for 4-6 days. The dialyzed product was freeze-dried to obtain a purified product, 3-maleimidopropionic acid-modified pullulan PL-MA. Step S3: Preparation of PDA@Zif-8-xAC (1) 3.94 g of 2-methylimidazole was weighed and dissolved in 40 mL of methanol solution. After stirring until completely dissolved, 1.31 g of zinc acetate dihydrate was added; stirring was continued at room temperature for 20-26 hours. After the reaction was completed, the mixture was centrifuged at a speed of 8000-9000 r / min for 8-12 minutes. The centrifugal precipitate was washed with methanol 2-4 times and vacuum dried at 55-65° C. for 12-14 hours. The obtained product was named Zif-8; (2) 0.2-0.4 g Zif-8 was added to 40-60 mL anhydrous ethanol and stirred for 2-4 h, then 0.2-0.4 g dopamine hydrochloride was added and stirred for 25-35 min, then 20-160 mg asiaticoside was added and stirred for 1-1.5 h, the pH of the solution was adjusted to 8.0-9.0 with 0.8-1 mol / L sodium hydroxide solution, and the stirring was continued for 22-26 h. After the reaction was completed, the solution was washed with anhydrous ethanol while being centrifuged for 8-12 min at a speed of 8000-9000 r / min. The centrifugal precipitate was vacuum dried, and the obtained product was named PDA@Zif-8-xAC; wherein x represents the concentration of asiaticoside added, in mg / mL; Step S4: preparing composite hydrogel Select the following method A or method B to prepare the composite hydrogel: Method A: First, 0.25 g of O-HACC and 0.2 g of PL-MA were dissolved in 5 mL of deionized water to form a 5 w / v% O-HACC homogeneous solution and a 4 w / v% PL-MA homogeneous solution, respectively. The two were then mixed in a certain proportion and allowed to stand to obtain a composite hydrogel. The obtained hydrogel was named O-HACC / PL-MAxy, hereinafter referred to as HPxy, where x and y represent the volumes of the O-HACC solution and the PL-MA solution added during gelation. Method B: Weigh 0.1 g of PDA@Zif-8-xAC powder and add it to a total volume of 5 mL of 4 w / v% PLMA solution, then mix it with an equal volume of 5 w / v% O-HACC solution to form a gel. The resulting hydrogel is named AA@O-HACC / PL-MA11, abbreviated as AA@HP11.
Citation Information
Patent Citations
Antibacterial adhesion injectable hydrogel dressing, preparation method and applications thereof
CN108912352A
Hydrogel, preparation method thereof and dressing
CN111154149A
Preparation method of microalgae self-oxygen-supply conductive antibacterial multifunctional hydrogel
CN117138102A
Multifunctional conductive injection hydrogel OQG and preparation method thereof
CN119139536A
Preparation and application of block cationic copolymer quaternary ammonium salt chitosan-based composite hydrogel
CN119192612A